Common security and defence policy of the European Union and readiness of the Republic of Serbia for integration - Cvetković Nenad (Војно дело, 2022)
Within the process of the European integrations in the sphere of defence, the Republic of Serbia is expected to adapt to the Common security and defence policy of the European Union regarding strategic and planning, and normative and legal conditions, as well as the construction of appropriate operational capacities for completing the tasks in the EU joint operations. This paper analyses the EU defence policy, the compatibility of The Republic of Serbia's defence policy with that of the EU, and the capabilities of the Serbian Armed Forces to meet the challenges of the current European integrations. It is assumed that Serbia has mostly adapted its planning and legal framework in the field of defence to the EU acquis, and that the Serbian Armed Forces have the resources which can meet the challenges of the European common defence. This paper is based on the analysis of the content of regulatory documents, the papers which had covered this topic, and comparative analysis of certain statistic indicators. It is evaluated that the European Union has not achieved the desired level of development of defence policy and capabilities, whereas Serbia can now largely meet the needs of European integrations in the field of defence.